2018
DOI: 10.1016/j.jvs.2018.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of diabetic wound healing with adipose-derived stem cells, endothelial-differentiated stem cells, and topical conditioned medium therapy in a swine model

Abstract: Cellular therapy with ASCs, EC/ASCs, and topical CM accelerated diabetic wound healing in the swine model. Enhanced angiogenesis and immunomodulation might be key contributors to this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
(27 reference statements)
1
39
0
1
Order By: Relevance
“…It should also be noted that our unique outcomes reveal the synergistic impact of PBM+ADS on skin injury repair in comparison with other related experiments that only investigated the impression of a solo cure with either PBM44 or ADS 18…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It should also be noted that our unique outcomes reveal the synergistic impact of PBM+ADS on skin injury repair in comparison with other related experiments that only investigated the impression of a solo cure with either PBM44 or ADS 18…”
Section: Discussionmentioning
confidence: 63%
“…Probes using animal simulation18 and studies in humans19 have been performed to display the probable favorable impacts of ADS in wounds and ischemic organs in animals and in patients who suffer from DM. Despite the current achievements, several chief obstacles remain before they can be effectively used to benefit diabetic ADS in wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to large animal models, particularly pigs, ASCs and their potential to improve cutaneous wound healing have been investigated in several studies [23,[100][101][102][103][104] [ Table 2]. James et al] [101] performed a dose-response study of allogenic porcine ASCs delivered into four-centimeter circular full-thickness excisional wounds.…”
Section: Wound Healing In Skinmentioning
confidence: 99%
“…Using a rat model of an ischemic wound (Fisher 344 rats, full-thickness excisional wounds created with a 6 mm punch biopsy), Cooper et al [61] reported that ASC-CM collected from ASCs cultured for 48 h in serum-free MSC basal medium and applied at 20 µL to each wound daily significantly accelerated ischemic wound closure compared to unconditioned medium. Irons et al [68] recently showed that after topical application of CM collected from ASCs isolated from the gluteal region of Yorkshire pigs, the diabetic wound healing in the same animals was significantly enhanced, with concomitant increased angiogenesis and immunomodulation. ASCs were cultured with M-199 medium with 10% FBS and then harvested at 90% confluence, and the cell pellets were resuspended with phosphate buffered solution (PBS).…”
Section: In Vivo Experimental Studiesmentioning
confidence: 99%